Socio-cultural Socialization of Disabled People and Persons with Disabilities: To the Formation of a New Open Society (International Journal of Psychosocial Rehabilitation, 2020)
Inclusion of disabled people and persons with disabilities becomes one of the most important conditions for the creation of a new open society. This is a society in which different social groups equally cooperate regardless of their personal potential and capabilities. The research, carried out by the authors of the article, proceeds from the hypothesis that an appeal to socio-cultural socialization technologies of disabled people and persons with disabilities allows the creation of a space of interaction and mutual understanding between them and the surrounding society. In the course of this interaction, it is possible to form a new culture of communication, educational activities, and a culture of public and professional activity in which persons with disabilities will be able to realize their potential. The aim of the research was to study the ways to overcome passivity in the behavior of persons with disabilities, increase their activity, and study their attitudes and expectations with regard to partners in the process of socio-cultural socialization. The main methods of research were the Internet survey of persons with disabilities, expert interviews with representatives of municipal authorities and public organizations of persons with disabilities, and in-depth interviews of disabled people and persons with disabilities. When analyzing the obtained data, methods of mathematical processing, grouping methods, and factor analysis were applied. The article presents the results of research on leisure preferences of persons with disabilities, the level of self-esteem, expectations and fears in relations with other social groups, and with society in general. The potential of social tourism in the process of socio-cultural socialization and the strength and possibilities of using social tourism technologies to enhance the position of disabled people were revealed. The obtained data could be useful for professionals working in the sphere of adaptation and rehabilitation of persons with disabilities, as well as for the disabled themselves, who are ready for more active self-realization. Results could be interesting for the public because many of the readers interact more or less with disabled people and persons with disabilities.